Pompe disease - What do we currently know about the disease? - Edyta Białowąs; Magdalena Mazurek; Artur Aghadi; Iwona Cuber; Ewelina Dybała; Karolina Szela (Journal of Education, Health and Sport, 2023)
• Introduction: Pompe disease (PD) is a rare metabolic disorder caused by a partial or complete deficiency of acid α-glucosidase (GAA) which leads to lysosomal accumulation of glycogen. Excessive amounts of glycogen accumulate mainly in the cells of the heart and skeletal muscles and cause dysfunction of these tissues. It is inherited in an autosomal recessive manner. The most common diagnostic methods include genetic tests and the measurement of enzyme activity in leukocytes or fibroblasts. A screening test is also available that tests the enzyme activity in dried blood spot (DBS). The treatment of PD is mostly based on synthetic GAA enzyme supply to the patients. The therapy reduces glycogen storage and improves muscle function, decreases heart size and prolongs the lives of those with infantile form of PD. In the adult onset of the disease treatment increases physical efficiency and reduces the progression of respiratory failure.